Biorrefinaria florestal : uma proposta para integração dos processos de obtenção de nanocelulose e etanol 2G a partir da polpa de celulose de eucalipto - Bondancia, Thalita Jessika (Universidade Federal de São Carlos, 2016)
The use of eucalyptus kraft as biomass for an integrated production of sugars and new added-value products such as nanocellulose, stands out a potential strategy for the implementation of a forest biorefinary, that can contribute to the diversification of the paper and cellulose sector. In this process configuration, amorphous cellulose is converted into sugars that can be used for second generation ethanol (2G) production, leaving a residual fraction of nanocellulose that can be applied in various sectors as a high-value product. In this context, the objective of this study was to evaluate the viability of integration of 2G ethanol production with nanocellulose, using eucalyptus kraft pulp as raw material. In the enzymatic hydrolysis step, the experimental central composite design (CCRD) was used as a tool evaluate the effects of solids loading (SL) from 5 to 22% (w/v), and enzymatic loading (EL), from 3 to 17 mg protein/g of cellulose, on the glucose released and cellulose conversion. Glucose concentrations from 45 to 130 g/L with conversions from 40 to 95% were obtained after 24 hours of enzymatic hydrolysis. The validation of the statistical model was performed at SL 20% and EL 10 mg/g cellulose, defined using desirability function as the optimum condition for obtaining high concentrations of sugars associated with residual material to favor the production of nanocelulose. The sugars released using the selected optimum condition (134 g/L) were used to produce 2G ethanol by fermentation using Saccharomyces cerevisiae, resulting in 62.14 g/L ethanol after 8 h (yield 95.5%). For all of the conditions evaluated, the residual solids presented cellulose nanofiber (NFC) characteristics, according to analysis by Scanning Electron Microscopy with Field Emission (SEM - FEG). Nanocellulose presented crystallinity index between 76% and 83% with initial degradation temperature around 320ºC. The use of a temperature reduction strategy from 50 to 35 ° C after 24 hours of enzymatic hydrolysis allowed to obtain cellulose nanocrystals (NCC) after 144h reaction. The crystallinity index of this material confirmed the presence of highly crystalline cellulose with initial degradation temperature around 330°C. The NCC showed length of 260 nm and diameter 15 nm, with aspect ratio L/D 15. Such characteristics are adequate for application as reinforcement in polymeric materials. Finally, enzymatic hydrolysis experiments were made in a stirred tank reactor (5L) using SL of 10 and 15% and EL of 5 and 10 mg/g cellulose, in order to obtain the parameters required to scale-up. The impeller used was the up-pumping and down-pumping Elephants Ears. The rotation of 470 rpm, defined by performing mixing time test, was used to evaluate the power consumption and apparent viscosity during of hydrolysis reaction. The residual solids of the hydrolysis at 5L scale presented nanocelulose with similar characteristics to the smaller scale (100 mL). In conclusion, the results obtained here showed that the integration of the processes for nanocellulose and 2G ethanol production is very promising and could contribute to implementation of the forest biorefineries and diversification of cellulose and pulp sector.
Keywords: Etanol; Nanocelulose; Hidrólise enzimática; Ethanol; Nanocellulose; Enzymatic hydrolysis; Forest biorefineries; ENGENHARIAS::ENGENHARIA QUIMICA